Detection of anti‐NS1 antibodies after pandemic influenza exposure: Evaluation of a serological method for distinguishing H1N1pdm09 infected from vaccinated cases. Issue 3 (19th January 2020) - Robertson, Anna Hayman; Mahic, Milada; Savic, Miloje; Tunheim, Gro; Hungnes, Olav; Trogstad, Lill; Lipkin, Walter Ian; Mjaaland, Siri
Abstract: Background: Reliable exposure information is crucial for assessing health outcomes of influenza infection and vaccination. Current serological methods are unable to distinguish between anti‐hemagglutinin (HA) antibodies induced by infection or vaccination. Objectives: We aimed to explore an alternative method for differentiating influenza infection and vaccination. Methods: Sera from animals inoculated with influenza viruses or purified H1N1pdm09 HA were obtained. Human samples were selected from a pregnancy cohort established during the 2009 H1N1 pandemic. Unvaccinated, laboratory‐confirmed cases (N = 18), vaccinated cases without influenza‐like‐illness (N = 18) and uninfected, unvaccinated controls (N = 18) were identified based on exposure data from questionnaires, national registries and maternal hemagglutination inhibition (HI) titres at delivery. Animal and human samples were tested for antibodies against the non‐structural protein 1 (NS1) and HA from H1N1pdm09, using a Luciferase Immunoprecipitation System (LIPS). Results: Anti‐NS1 H1N1pdm09 antibodies were detected in sera from experimentally infected, but not from vaccinated, animals. Anti‐HA H1N1pdm09 antibodies were detectable after either of these exposures. In human samples, 28% of individuals with laboratory‐confirmed influenza were seropositive for H1N1pdm09 NS1, whereas vaccinated cases and controls were seronegative. There was a trend for H1N1pdm09 NS1 seropositive cases reporting more severe and longer duration of symptomatic illness than seronegative cases. Anti‐HA H1N1pdm09 antibodies were detected in all cases and in 61% of controls. Conclusions: The LIPS method could differentiate between sera from experimentally infected and vaccinated animals. However, in human samples obtained more than 6 months after the pandemic, LIPS was specific, but not sufficiently sensitive for ascertaining cases by exposure.